Clement of Alexandria and the Beginnings of Christian Apophaticism. By Henny Fiskå Hägg - Gould, Graham (The journal of theological studies, 2007)
Clement's apophaticism is an appealing subject and is well served by this clear, pleasantly written, and relatively brief monograph, whose relatively high number of pages reflects a large typeface rather than great length. More than half of the book is in fact devoted to introductory questions: Clement's life and context, the concept of God in Middle Platonism, and the method of the Stromateis (including discussion of Clement's concealment of doctrines and preference for oral teaching, and of the questions raised by the Secret Gospel of Mark). The remaining four chapters concern Clement's apophaticism as applied to the being of the Father, the doctrine of the Logos, the means by which knowledge of God is attained, and the distinction between the essence and power of God.